Utilizing Gamification “Duolingo” to Enhance Motivation in Learning English Vocabulary among Adults - Agustine Andriana Ayu Mahardika; Putu Sita Witari (English Department FBS UNP, 2025)
Learning English may be beneficial for adults to explore many things and communicate with others. A strong knowledge of English vocabulary is needed to fulfill those purposes. However, adults may think that they have no time to learn English. Therefore, gamification has become one of the best ways to learn English vocabulary. One of the gamification tools that can be used to learn is Duolingo. Duolingo is a game-based application to help people learn a foreign language, especially English. One research question is presented in this research: “What factors affect adults to use Duolingo to enhance motivation in learning English vocabulary? This research aims to find out factors that affect adults to utilize Duolingo to improve their motivation in learning English vocabulary. This mixed method of research used a close-ended questionnaire containing 17 items of Likert-scale statements and an in-depth interview to gather the data. The Likert-scale questionnaire was distributed to 41 participants and the online Zoom meeting was conducted with 3 participants. This research applies TKT 3 which aims to prove the concept (proof-of-concept) of important functions and/or characteristics analytically and experimentally. The findings displayed that the game features present some beneficial impacts for the users such as better understanding in learning English vocabulary. It is expected that future researchers employ many participants so the results can be specified and used in broader educational contexts.